2019
DOI: 10.3389/fpsyg.2019.01855
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Child Perfectionism and Psychological Disorders

Abstract: Objective: Perfectionism is one of the variables related to the correct emotional development or with the appearance of clinical symptomatology in childhood. A study has been designed to evaluate the differential effect that each dimension of perfectionism (external pressure, self-exigency, and negative self-evaluation) has in a Spanish children sample of general population for each of the following clinical aspects: irritability, worthlessness feelings, thinking problems, and psychophysiological symptoms.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
3
6
0
Order By: Relevance
“…As expected, the presence of elevated levels of perfectionism was associated with psychological difficulties in children [7,11,14]. Specifically, these children were more likely to suffer from emotional and behavioral problems and adjustment difficulties than children with low perfectionism.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As expected, the presence of elevated levels of perfectionism was associated with psychological difficulties in children [7,11,14]. Specifically, these children were more likely to suffer from emotional and behavioral problems and adjustment difficulties than children with low perfectionism.…”
Section: Discussionsupporting
confidence: 68%
“…Based on the previous literature [21,[23][24][25], we hypothesize that gender differences will be found, but not by age. Furthermore, we expect children with high perfectionism to show greater psychological difficulties and lower prosocial behavior than low perfectionism children [7,14,30,35]. Lastly, we consider the SOP-Critical and SPP dimensions to be the most predictive of psychological difficulties, especially emotional symptoms and behavioral problems, respectively [7,13,27,35].…”
Section: Introductionmentioning
confidence: 99%
“…In the present research study, we investigated the internal validity of the PI (Hill et al, 2004 ) in an occupation that encourages perfectionistic tendencies in own behavior or in students' behavior (Shim et al, 2020 ). Our focus on teacher perfectionism was motivated by the fact that previous studies reported that it is a powerful predictor for teacher efficiency and teacher burnout (Craioveanu, 2014 ; Ghorbanzadeh and Rezaie, 2016 ), and can have an impact on students' variables (Lozano et al, 2019 ). We collected data from a large sample of schoolteachers, and we analyzed the factor structure of the PI (Hill et al, 2004 ) using confirmatory factor analyses.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main arguments for conducting this research. First, perfectionism is an important teacher variable that is associated with teaching efficacy and teacher burnout (Ghorbanzadeh and Rezaie, 2016 ), while teacher pressure to perform was found to be related to clinical symptoms in students (Lozano et al, 2019 ). This means that accurate assessment of teacher perfectionism can be important for understanding both teacher-related and student-related variables.…”
Section: Introductionmentioning
confidence: 99%
“…Different dimensions of perfectionism include excess concern over mistakes, personal standards, parental expectations, parental criticism, and doubts about actions and organization ( 26 ). It has been proposed that when a child with such personality traits make mistakes that are not accepted in their environment or when they feel incompetent to handle any demanding situation, a cognitive scheme might be activated, favoring distorted judgments of reality, leading to self-perceptions of worthlessness and incompetence, irritability and therefore increasing the thinking problems as well as the corresponding physiological symptoms ( 27 ).…”
Section: Pathophysiologymentioning
confidence: 99%